2012
DOI: 10.1007/s00464-012-2273-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic balloon dilatation for benign fibrotic strictures after curative nonsurgical treatment for esophageal cancer

Abstract: EBD for stricture after nonsurgical treatment of esophageal cancer was safe and effective. However, patients with benign strictures after nonsurgical treatment required significantly longer time to recover from dysphasia compared to those after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 23 publications
2
53
0
Order By: Relevance
“…A multivariate analysis has shown that circumferential tumor extension of more than three-quarters of the lumen is a risk factor for post-operative stricture after esophageal ESD (5). Patients suffering from dysphagia undergo repeated endoscopic dilation, such as endoscopic balloon dilation (EBD) or dilation with a bougie, for a long period if they have severe esophageal stricture due to extended ESD (3,6,7). Multiple sessions of endoscopic dilation cause substantial suffering for patients, discomfort in the dilation session and increased risk of bleeding or esophageal perforation, as well as potentially being more expensive (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multivariate analysis has shown that circumferential tumor extension of more than three-quarters of the lumen is a risk factor for post-operative stricture after esophageal ESD (5). Patients suffering from dysphagia undergo repeated endoscopic dilation, such as endoscopic balloon dilation (EBD) or dilation with a bougie, for a long period if they have severe esophageal stricture due to extended ESD (3,6,7). Multiple sessions of endoscopic dilation cause substantial suffering for patients, discomfort in the dilation session and increased risk of bleeding or esophageal perforation, as well as potentially being more expensive (7).…”
Section: Introductionmentioning
confidence: 99%
“…Patients suffering from dysphagia undergo repeated endoscopic dilation, such as endoscopic balloon dilation (EBD) or dilation with a bougie, for a long period if they have severe esophageal stricture due to extended ESD (3,6,7). Multiple sessions of endoscopic dilation cause substantial suffering for patients, discomfort in the dilation session and increased risk of bleeding or esophageal perforation, as well as potentially being more expensive (7). To avoid or minimize the disadvantages, the prevention of esophageal stricture after extended ESD is needed.…”
Section: Introductionmentioning
confidence: 99%
“…This study involved the artificial creation of long esophageal strictures (> 20 mm) in a porcine model. A small clinical study found that strictures of this length are at high risk of becoming refractory [14]. Therefore, this animal model is similar to refractory esophageal strictures observed in human patients.…”
mentioning
confidence: 50%
“…Most authors defined clinical success as resolution of dysphagia (or tolerance of soft diet) measured by different scores [2, 12, 14-16, 18, 19], often requiring a variable dilation-free period [11,13,18,20,21] and considering percutaneous endoscopic gastrostomy (PEG) status [20,22,23]. Francis et al [22] also reported patient satisfaction with the dilation program.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the variable concept of efficacy, it is known that the majority of patients with benign strictures will be effectively treated with up to five dilations [15], but about one-third of patients will develop recurrent dysphagia af- ter dilation within the first year, and 10% of patients will need ongoing dilations to become dilation free [14,16,18]. On the other hand, only 1 out of 3 refractory benign strictures will achieve clinical resolution defined as no need for endoscopic dilation, surgery, or PEG for a 6-month period [20].…”
Section: Introductionmentioning
confidence: 99%